An Analysis of Code Switching Found in Novel “The Paragon Plan” - I Kadek Wika Ardianta; I Komang Sulatra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
Bilingualism is native-like control of two languages. Has even suggested that Bilingualism commences when a person begins to understand utterances in a second language. Code-switching frequently occurs if the speakers can speak more than one language and use the languages simultaneously in the same context. This means the speakers intend to keep the utterance's meaning the same when emphasizing the purpose. In this research, the data was collected by using the observation method. The data of this study were taken from The Paragon Plan novel by Aranindy. The data was analyzed based on a theory proposed by Poplack (1980) to find out and categorize the types of code-switching. Meanwhile, the reasons for code-switching were analyzed by using the theory by Hoffman (1991). In analyzing the data, descriptive and qualitative methods were used. The types of inter-sentential switching are the most dominant in the novel The Paragon Plan with 30 data or 44.8%, followed by inter-sentential switching with a total of 24 data or 35.8%, and followed by tag switching amounted to 13 data or 19.4% of 67 data. Concerning the seven reasons for code switching, the findings indicate that only two were identified in the novel “The Paragon Plan”. Talking about particular topic is the most dominant reasons of code switching. Ultimately, code-switching in a novel can serve various narratives, character-building, and stylistic purposes. It enriches the story's linguistic and cultural landscape, making it more engaging and relatable for readers.